Malāmat and the Ethics of Invisibility: Mysticism, Poetic Witnessing, and Moral Critique in Late Modernity - Harmanci, Mahmut Esat; Harmanci, Meric (MDPI, 2026)
This article reconceptualizes mal & amacr;mat not as a marginal Sufi discipline but as a distinct ethical paradigm that redefines the relationship between selfhood, action, and moral legitimacy. Situating the discussion within late-modern conditions shaped by technological mediation, algorithmic evaluation, and regimes of visibility, it argues that ethical value has increasingly been externalized through performance, recognition, and quantifiable outputs. Against this background, mal & amacr;mat is examined as an alternative ethical model grounded in inward vigilance, relational practice, and the deliberate concealment of virtue. Drawing on early Mal & amacr;mat & imacr; texts-particularly al-Sulam & imacr;-and their later elaboration in Ibn Arab & imacr;, the study demonstrates that ethical subjectivity is constituted through continuous self-critique and responsibility before the Divine rather than through public validation. The argument is further developed through a comparative engagement with Aristotle, Kant, Kierkegaard, and MacIntyre. It shows that, unlike these frameworks, mal & amacr;mat sustains ethical life as an ongoing tension rather than a state of equilibrium or a universalizable norm. The article also highlights the role of classical Turkish and Persian poetry-especially Fuz & ucirc;l & icirc;, N & acirc;b & icirc;, and & Scedil;eyh G & acirc;lib-in articulating mal & amacr;mat as a lived ethical sensibility. Ultimately, the study proposes mal & amacr;mat as a critical counter-model to contemporary regimes of visibility, offering an ethics grounded in inwardness, concealment, and irreducible personal responsibility.
Keywords: mal & amacr; mat; sufism; ethics of invisibility; moral subjectivity; visibility regimes; Islamic ethics; Ottoman poetry; mysticism; late modernity; ethical selfhood; Religion